The logical status of history and the paradoxes of historicism - Demetriou, Kyriakos (Dia-noesis: A Journal of Philosophy, 2024)
Much of the philosophical project of Leo Strauss involved an attempt to restore pre-modern philosophy, yet the impetus for the reconsideration of the interpretative textual methodologies was undeniably of a modern complexion. Strauss not only took historicism as a threat to philosophy, as it replaced philosophic questions with historical questions, but also as a source for the intellectual crisis of the West. Over and above 20th-century political crisis there was an intellectual crisis, not unrelated to the belief in the mutability of values, in moral relativism resulting in a kind of nihilism. In a nutshell, historicism, in assuming that all human thought is historical, rejected the idea of philosophy as the attempt to grasp fundamental problems coeval with human thought – a rejection that ultimately amounts to a full critique of human thought as such. In his massive work, in both his historical and his strictly philosophical writings, Strauss pursued the restoration of political philosophy as a meaningful and urgent enterprise.